Analysis of the inaccuracy of the prosedure code for outpatient BPJS patients in 2024 at Dr. Harjono S. Hospital, Ponorogo Regency - Anggraini, Ivana Salsabila Myrilla; Novratilova, Sinta (Institute of Computer Science (IOCS), 2025)
The implementation of the Indonesian Case Based Groups (INA-CBG) system is a crucial instrument in the National Health Insurance (JKN) program for the payment of health service claims at advanced referral health facilities (FKRTL). The success of this system depends heavily on the accuracy of the codification of the diagnosis (ICD-10) and the action/procedure (ICD-9-CM) which is a representation of the service output. Code accuracy is not only essential for the collection of claim costs, but also plays an important role in nursing care, improving service quality, and analyzing morbidity-mortality data. A preliminary study at Dr. Harjono S. Ponorogo Hospital in January-February 2025 found 12 outpatient claim files (cardiac and neurological polys) in the June-August 2024 period with inaccuracies in the code of procedure, including 10 files that were not coded and 2 files that were incorrectly coded. Furthermore, initial observations through interviews with internal verifiers indicated the absence of a Standard Operating Procedure (SPO) for coding BPJS patients and the absence of coding evaluations from internal parties and hospital management. Based on these problems, this study aims to analyze the factors that cause the inaccuracy of the procedure code of outpatient BPJS patients at Dr. Harjono S. Hospital, Ponorogo Regency.